GENDER DISCRIMINATION IN SHASHI DESHPANDE'S THE DARK HOLDS NO TERROR - S., Akila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Dark Holds No Terror by Shashi Deshpande this novel entitled Gender Discrimination and how it evolves it in the novel 'Dark Holds No Terror'. Gender discrimination is when someone is treated unequally or disadvantageously based on their gender but not necessarily in a sexual nature. The female character too finds it difficult to adjust with modern society. The patriarchy changed modern life style and empowerment of women made the men character feel inferior to women characters. Sarita, the female protagonist of the novel, is seen as strong compared to her husband Manu. Her economic independence and her position as a well-established doctor made her husband feel inferior. Being the head of the family, Manu wants to have control over his wife Sarita, unconsciously develops a strange behaviour which leads to sexual sadism. Deshpande ‘s men characters are weak compared to her female protagonists. The Dark Holds No Terror depicts the women's world in an authentic, realistic and credible manner. This research paper highlights the fact that it is not the circumstances that contribute to the negation of women ‘s rights; but the fact is that it is their women folk who polarise their dig at the emancipation of women.